(untitled) (Journal of Libya for geographical studies, 2024)
Studying the geographic distribution of the population is important. For its role in recognizing population distribution patterns and responding to urban needs and problems. Dasymetric maps provide accurate estimates of population distribution and highlight the variation in density within the areas of the administrative unit. Therefore, the study aims to identify the levels of population density in the city of Sebha using decimetric maps. The importance of the study lies in producing a dasymetric map that reflects the actual distribution of population in geographical space and highlights the variation of density within areas. Administrative unit. The study relied on the descriptive analytical approach, and we used the multi-category method to create a dasymetric map of population distribution, by modeling the data within a geographic information systems environment. The results showed that the density map of Sebha shows an accurate representation of population distribution, as it excluded uninhabited and non-residential areas, which represented 79% of the total area (2006 AD) and 62% (2022 AD), and density levels varied within neighborhoods depending on the housing type. It shows that the population distribution tends to spread horizontally across space. The estimated values of the city’s dasymetric density were close to the actual values, which indicates the effectiveness of satellite visualization and GIS technology in producing decimeter density maps.